The evaluation of a new haematological cell counter, the CELL-DYN 3500, on canine leukocyte differential counts - Reyers, Fred (University of Pretoria, 2013)
Dissertation (M Med Vet (Clinical Laboratory Diagnostics))--University of Pretoria, 2001.